2014
DOI: 10.1186/1471-2458-14-1308
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adherence to antiretroviral therapy among people living with HIV and AIDS at the regional hospital of Sokodé, Togo

Abstract: BackgroundAdherence to antiretroviral therapy (ART) is beneficial in reducing the risk of emergence of HIV resistant strains. Adherence to ART among Persons Living with HIV/AIDS (PLWHA) is influenced by several factors related to the patient, the medication, and health facilities. In Togo, previous studies on adherence to ART have reported good adherence to ART during the first year of follow-up. However these may hide many disparities dues to cultural specificities which may differ across geographic areas of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
50
3
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 26 publications
13
50
3
6
Order By: Relevance
“…Lower education was found to have associations with barriers to receiving HIV related health care, including ART. Other studies have been previously reported from African settings where the level of education has adversely affected adherence [19,27] similarly with what has been reported in the current study that those with secondary education and higher in this study had poor ART adherence compared to those with primary education. Educated participants are more likely to be employed and their time at work influencing negatively with the consistent use of medication.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Lower education was found to have associations with barriers to receiving HIV related health care, including ART. Other studies have been previously reported from African settings where the level of education has adversely affected adherence [19,27] similarly with what has been reported in the current study that those with secondary education and higher in this study had poor ART adherence compared to those with primary education. Educated participants are more likely to be employed and their time at work influencing negatively with the consistent use of medication.…”
Section: Resultssupporting
confidence: 90%
“…However, other factors associated in India whereby 56% of the educated participants said that HIV could probably be controlled by ART [5]. Other literatures support that ART adherence rate was higher among participants who had a high level of formal education [19,25]. Our findings are inconsistent with that reported by Kalichman in United States of America, who had earlier identified low educational status as a major factor of poor adherence to ART [26].…”
Section: Resultscontrasting
confidence: 88%
See 2 more Smart Citations
“…(1) Regarding adherence to pharmacological treatment, it was observed that most patients had adequate adherence to ART, diverging from the previous research. (19)(20)(21) This result may be related to the fact that only 12 individuals in this study were classified as in harmful use of alcohol, probably due to the small number of people.…”
Section: Discussionmentioning
confidence: 79%